Multiculturalism and Socio-Cultural Harmonization - Al Miqdad, Muhammad Ardi; Biati, Lilit; Baihaqi, Agus; Al Hamidi, Muhammad Fauzi (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study examines multiculturalism and socio-cultural harmonization in the religious life of Kampung Pancasila, Patoman Village, Banyuwangi. The research aims to analyze how local wisdom fosters tolerance and harmony among diverse religious communities, including Islam, Hinduism, Buddhism, and Christianity. A qualitative descriptive method was employed, combining field observation, interviews with local leaders and residents, and document analysis. The findings reveal that social harmony in Patoman is deeply rooted in cultural traditions and the community’s historical identity as a “meeting place” (patoman). The implementation of Pancasila values plays a crucial role in guiding social interaction, preventing conflict, and maintaining peaceful coexistence. Harmonization is also expressed through cultural arts such as Gandrung dance, Balinese music, and religious practices that coexist without tension. This study concludes that Patoman Village represents a living model of multiculturalism and tolerance, offering significant lessons for promoting social cohesion and sustaining Indonesia’s unity.